Analysis Quality System Information Accounting: Influencing Factors and Their Impact on Information Accountancy - Sadiyah, Lina Halimatus; Ladewi, Yuhanis; Hari, Kurnia Krisna (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2024)
This study aims to determine and analyze the factors that affect the quality of accounting information systems in improving the quality of accounting information at (Perum Bulog, South Sumatra & Babylon Regional Office in Palembang City). The type of research used in this study is qualitative descriptive research. The variables used in this study consist of factors in the use of information technology, internal controls factors, commitment factors to the organization, quality of information systems, and quality of accounting information. The data used in this study used primary and secondary data. Data collection techniques are through interviews and documentation. The data analysis technique used is qualitative analysis. The results of this study are Factors that affect the quality of accounting information systems in improving the quality of accounting information, namely the use of technology factors greatly affect the quality of accounting information systems to improve the quality of accounting information by reducing the risk of errors and improving financial data management. Internal control factors greatly affect the quality of accounting information systems by implementing good internal controls, the risk of errors and misuse can be reduced, thus improving the overall quality of accounting information. The commitment factors to the organization are very important in improving the quality of accounting information systems with the use of systems that are used effectively, which will improve the quality of accounting information US a whole. The quality of accounting information systems can improve the quality of accounting information, reduce the risk of errors, and increase the accuracy and reliability of financial information. The improved quality of accounting information systems will result in higher-quality accounting information.